Innovation to Improve Competitiveness of SMES of Leather Bags Combined with Batik and Tenun in Malang City - Galuh, Ajeng Kartika; Sudjatmiko, Sudjatmiko (International Journal of Social and Local Economic Governance, 2017)
Some problems faced by micro-small-medium enterprises (SMEs) of leather bags combined with batik and tenun (Indonesian weave) in Malang become the concern of this paper. In producing products, some enterprises still use simple technology. The products, therefore, have low quality which influences their competitiveness in market. In addition, there is no finance access to bank to increase their business scale. In order to solve the problems and give total solution, technology and capital aids are offered to the enterprises. As well as intermediate technology which is in the form of roll press machine and sewing assembling machine with a large wheel provided to make the products neater and stronger, training on simple business transaction recording is applied to prevent a problem regarding finance access to bank.Keywords: Innovation, Competitiveness of SMEs, Intermediate Technology